Phase stability and structural properties of heat treated FeCoNiAlSi0.5 high-entropy alloy - Nagarjuna, Cheenepalli; Dewangan, Sheetal Kumar; Lee, Hansung; Mohan, Man; Jain, Reliance; Song, Eunhyo; Ahn, Byungmin (Materials Today Communications, 2025)
The present study explored the effect of heat treatment on phase stability, microstructure, and mechanical properties of FeCoNiAlSi0.5 high-entropy alloy (HEA) processed by mechanical alloying (MA) and spark plasma sintering (SPS). The results revealed the formation of a single-phase body-centered cubic (BCC) structure after 30 h of milling and the subsequent sintering process. Further, heat treatment at higher temperatures stabilizes the BCC phase and promotes the formation of a more homogeneous microstructure. The experimental results revealed that the maximum Vickers hardness for the sintered HEA was approximately ∼1036 HV, while the ultimate compressive strength of ∼3374 MPa was obtained for the HEA heat treated at 1000°C. The nanoindentation tests provided the peak nanohardness (∼11.94 ± 0.63 GPa) and elastic modulus (258 ± 10.13 GPa) for the sintered HEA. The creep resistance improved up to 900°C and then slightly reduced for the HEA heat treated at 1000°C due to microstructural coarsening. Therefore, this study demonstrated that the HEAs exhibited excellent stability in terms of phase, microstructure, and mechanical properties, making these alloys ideal candidates for high-temperature applications.
Keywords: Body-centred cubic; Cubic structure; Effect of heat treatments; High entropy alloys; Mechanical; Mechanical behavior; Microstructures and mechanical properties; Property; Single phasis; Spark-plasma-sintering; Heat treatment; High-entropy alloys; Mechanical behavior; Microstructure; Powder metallurgy